A two-phase decision-making model for product development based on a product-oriented knowledge inventory model. Issue 4 (9th July 2021) - Sadeghi Dastaki, Mohsen; Afrazeh, Abbas; Mahootchi, Masoud
Abstract : Purpose: Over the past years, many studies have explored the role of knowledge management (KM) in companies. KM is concerned with the measurement of knowledge to manage knowledge efficiently. On the other hand, the intangible nature of knowledge makes its measurement challenging. Furthermore, there is no standardized method to measure knowledge, and it is chiefly measured based on the subjective judgment of researchers. Moreover, New Product Development (NPD) departments in many companies strive to assess their knowledge in terms of company products and knowledge workers. Hence, this study aims to propose a product-based two-phase technique that measures the company knowledge inventory. Design/methodology/approach: In the first phase, the value of knowledge is quantified relative to products, knowledge workers and the entire company using two concepts of knowledge width and depth. Then, a three-dimensional knowledge asset map (knowledge, products and knowledge worker dimensions) is designed to assess and audit knowledge workers. Finally, this technique recruits an integer linear programming model with a cost minimization objective function to optimize the supply of NPD knowledge requirements in the second phase. Findings: This model enables managers to determine what type of knowledge can be supplied by existing knowledge workers, whether within the company or by other external sources. Originality/value: Among existing knowledge measurement methods, only a few use a product-based measuring technique. However, they fail to offer suitable scenarios for managers' decision-making process and consider cost structures in measurement techniques. Hence, this paper attempts to overcome these drawbacks.